INDIA'S TRADE PERFORMANCE IN THE MODI ERA (2014-2024): AN EMPIRICAL ANALYSIS OF TRADE AGREEMENTS, EXPORT-IMPORT DYNAMICS, AND ECONOMIC GAINS - Jaiswal, Amit (International Journal of Research -GRANTHAALAYAH, 2025)
This paper examines India's trade performance during Prime Minister Narendra Modi's tenure from 2014 to 2024, analyzing the impact of Free Trade Agreements (FTAs), bilateral trade partnerships, and structural reforms on export-import dynamics. Using data from the Reserve Bank of India, Economic Surveys (2022-23, 2023-24), and peer-reviewed journal articles, we document India's evolution from a merchandise export value of USD 422 billion in FY 2021-22 to USD 437 billion in FY 2023-24, with combined goods and services exports reaching USD 776.68 billion. Despite a persistent merchandise trade deficit averaging USD 240-267 billion, India achieved a robust services trade surplus of USD 162 billion in FY 2023-24. The analysis reveals that three new FTAs (Mauritius CECPA 2021, UAE CEPA 2022, Australia ECTA 2022) contributed to trade diversification, though their impact on overall export growth remained marginal. The study finds that India's share of global goods exports improved from 1.7% (2016-20 average) to 1.8% in FY 2023-24, while services exports grew remarkably, positioning India as the world's seventh-largest services exporter with a 4.3% share of global services trade. Key findings indicate that FTA partners performed marginally better than non-FTA partners, trade openness increased from 37.5 to 45.9 over two decades, and the Current Account Deficit improved significantly from 2.0% of GDP (FY 2022-23) to 0.7% (FY 2023-24). Policy implications emphasize the need for addressing non-tariff measures, strengthening MSME participation in FTAs, and building institutional capacity for better trade agreement utilization.